First case of New Delhi metallo-β-lactamase in Klebsiella pneumoniae from Ecuador: An update for South America. (December 2017) - Romero-Alvarez, Daniel; Reyes, Jorge; Quezada, Viviana; Satán, Carolina; Cevallos, Nelson; Barrera, Sofía; Trueba, Gabriel; Escobar, Luis E.; Villacís, José E.
Highlights: The New Delhi metallo-β-lactamase (NDM) resistance plasmid has autochthonous circulation in Ecuador. A Klebsiella pneumoniae ST147 harboring the NDM-1 gene in an IncA/C plasmid is described for the first time in Quito, Ecuador. The circulation of NDM in South America has been addressed mainly by Brazil and Colombia. Abstract: Objectives: To describe a clinical case of Klebsiella pneumoniae harboring a New Delhi metallo-β-lactamase (NDM) plasmid in Ecuador and to present a map of reports of NDM isolates in South America. Methods: The modified Hodge test, carbapenem inactivation method, imipenem–EDTA disk method (synergy), and Rapidec Carba NP test were used to identify antibiotic resistance mechanisms. The presence of resistance genes was explored with a conjugation assay, and molecular confirmation of NDM was performed by PCR and DNA sequencing. Plasmid characterization was conducted by PCR-based replicon typing. A literature review was performed in Google Scholar and PubMed to identify reports from South America. Results: An HIV-infected patient, who had never traveled abroad, developed a bloodstream infection caused by K. pneumoniae ST147 harboring the NDM-1 resistance gene in a plasmid from the IncA/C group. Local circulation of NDM has also been described in other South American countries, in particular in Colombia and Brazil, although published scientific records were not found for other countries. Conclusions: This report presents the first evidence of autochthonous circulation of the NDM-1 resistance gene harbored by an IncA/C plasmid isolated from a K. pneumoniae ST147 in Ecuador. Efforts should be implemented to monitor and characterize the spatial and temporal distribution of NDM in Ecuador and other countries of South America.